FAKTOR RISIKO STUNTING PADA ANAK BALITA DI KABUPATEN LAMPUNG TENGAH - Kristanti, Milantika; Fithri, Nayla Kamilia (Poltekkes Kemenkes Tanjung Karang, 2021)
Stunting is stunted growth in children due to malnutrition. It can affect children's cognitive and physical development, increase the risk of infection, and significantly contribute to child morbidity and mortality. This study aims to analyze the risk factors for stunting in children under five (13-59 months). The study used a case-control design to compare previous exposure to stunting and normal children under five. Measurements and interviews were conducted with 120 children under five and their mothers. The SPSS (24.0) was used for the Chi-square and Odds Ratio (alpha = 5%) test. The study found the risk factors for stunting under five, poor income (OR = 4.75; 95% CI 2.18-10.33), not getting exclusive breastfeeding (OR = 5.29; 95% CI 2.39-11.68) ), there is no access to clean water (OR = 3.00; 95% CI 1.42â€“6.32), and healthy latrines (OR = 3.73; 95% CI 1.75-7.94). Increasing the nutritional status of pre-pregnant and pregnant women and access to clean water and healthy latrines to prevent infection is an urgent need to be implemented immediately.Â